MEMBANGKITKAN POTENSI DIRI DAN MINAT SISWA DALAM BELAJAR BAHASA ARAB DENGAN NILAI-NILAI HYPNOTEACHING - Akhsan Akhsan; Ahmadi Muhammadiyah (Fakultas Tarbiyah Universitas Ibrahimy, 2021)
The most important obstacle today in learning Arabic is that the awareness of the importance of Arabic in students has not been fully formed. This fact occurs because Arabic learners and teachers, especially in Indonesia, are still trapped in policies (regulations regarding the continuity of learning in class, time and space issues), curriculum (objectives and boundaries of competence), and methodology (theories that must be put into practice). Coupled with the